Răspuns :
2^(2n+1) =2^(2n) ·2 = (2^2)^n·2=4^n·2 = 2·4^n
3^(2n+3) = 3^(2n)·3^3 = (3^2)^n·27 = 9^n·27 = 27·9^n
9^(n+1) =9·9^n
A = 2·4^n ·27·9^n - 4^n·9·9^n = 54·36^n - 9·36^n = 36^n(54 - 9) =
= 36^n · 45= 45 · 36^n = 45 · 36 · 36^(n-1) = 45·6·6·36^(n-1) =
=270·6·36^(n-1) ∈ M₂₇₀ .
3^(2n+3) = 3^(2n)·3^3 = (3^2)^n·27 = 9^n·27 = 27·9^n
9^(n+1) =9·9^n
A = 2·4^n ·27·9^n - 4^n·9·9^n = 54·36^n - 9·36^n = 36^n(54 - 9) =
= 36^n · 45= 45 · 36^n = 45 · 36 · 36^(n-1) = 45·6·6·36^(n-1) =
=270·6·36^(n-1) ∈ M₂₇₀ .